2009
DOI: 10.1016/j.jjcc.2008.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Stroke secondary to calcific bicuspid aortic valve: Case report and literature review

Abstract: Embolization from calcific bicuspid aortic valves can lead to stroke and MI. Conservative management with anticoagulation for treatment of associated poststagnation thrombosis or aortic valve replacement as treatment is debatable. This patient was successfully managed with anticoagulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 9 publications
0
9
0
1
Order By: Relevance
“…517 Pathological studies have demonstrated microthrombi on damaged aortic valves, which suggests a possible source for emboli, 518 but the clinical significance is uncertain.…”
Section: 511mentioning
confidence: 99%
“…517 Pathological studies have demonstrated microthrombi on damaged aortic valves, which suggests a possible source for emboli, 518 but the clinical significance is uncertain.…”
Section: 511mentioning
confidence: 99%
“…From existing series, it has become evident that a diseased aortic valve is a source of emboli. The degree of stenosis, calcification and regurgitation can be responsible for embolic stroke by damaging red blood cells through release of adenosine phosphate and thromboplastin with cloth formation [13,14,39] but also through turbulence and by dislodging calcified fragments [39]. These preoperative incidents serve as predictor for postoperative TE events [10,24].…”
Section: Discussionmentioning
confidence: 99%
“…Embolization from calcific BAVs may lead to stroke and myocardial infarction. Conservative management with anticoagulation, to treat associated post-stagnation thrombosis, or aortic valve replacement as the treatment, is debatable [97].…”
Section: Thromboembolismmentioning
confidence: 99%